The influence of using platelet rich plasma for post-extraction wound healing process - Oscar, Franky; Mangundjaja, Sunardhi; Yusuf, Makmuri; Pontjo, Bambang (Universitas Padjadjaran, 2010)
Wound healing process characterized by specific processes of inflammation, proliferation, and maturation. It was coordinated by the regenerating and healing factors, including growth factor. Platelet-rich plasma was a blood component that separated from blood cell plasma, which contains a lot of growth factors for increased wound healing. The objective of this research was to observe the effect of the application of platelet-rich plasma for wound healing. The true experimental factorial design research was done to 24 rabbits (Oryctolagus cuniculus) which have been performed tooth extraction and application of platelet-rich plasma. These rabbits were terminated on 3rd, 7th, and 14th day, and the lower jaw region where the tooth had been extracted were cropped stained with hematoxylin-eosin for fibroblast and collagen histopathology examination. Based on ANOVA statistical analysis, the mean of fibroblast on the experimental group was 52.00+19.18 higher than the control group 24.83+10.46. Statistical tests showed a significant result of platelet-rich plasma application to fibroblast amount (p < 0.001). Collagen mean on the experimental group was 30.25+9.33 higher than the control group 13.75+6.96. It was significant statistically (p = 0.001). The conclusion of this research that wound healing process was influenced by the application of platelet-rich plasma.